Efektivitas Pelatihan Power Point Untuk Meningkatkan Keterampilan Anak Didik Panti Asuhan Sakinah - Setiawan, Santoso; Kadafi, Abdul Rahman; Tuslaela; Purnamasari, Indah (Jurnal Pengabdian UntukMu NegeRI, 2023)
Power Point training is a training designed to assist participants in mastering the skills in using presentation software, namely Microsoft Power Point. In this training, participants will learn how to create interesting and effective presentations using Power Point. The material taught in Power Point training includes how to create attractive presentation slides using images, text, graphics, tables, and other media. In addition, participants will also be taught how to present information clearly and easily understood by the audience. This training will also discuss good slide layout, the use of animation and transitions, and effective presentation techniques. Participants will learn how to create engaging and memorable presentations using these techniques. By attending Power Point training, participants will be able to improve their presentation skills and create more interesting and effective presentations. Participants will get tips and tricks from the instructor in using Power Point. Keywords: Training, Power Point, Presentation